2016
DOI: 10.17750/kmj2015-638
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia - abdominal hypertension syndrome in pregnancy. whether a hypothesis will become a theory?

Abstract: Based on the analysis of literature and their own data the authors presented modern aspects of the etiology and pathogenesis of preeclampsia from the perspective of intra-abdominal hypertension syndrome. The data are collected from a large representative sample of 647 patients at various stages of gestation. It was shown that elevated levels of intra-abdominal pressure at 20-24 weeks of pregnancy in some cases preceded the development of preeclampsia. The level of intra-abdominal pressure, preceding the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…It limited the venous return, so measuring IAP could be useful in prenatal care. Similarly, the findings confirmed by pre-eclampsia study Marshalov, et al, (2016) in which the data was a large representative sample of "more than six hundred" patients at various stages of gestation and demonstrated that an increase in intra-abdominal pressure at 20-24 weeks of pregnancy preceded the development of preeclampsia with significantly as higher than regular patients (p <0.001) and the rate of its elevation considered as an essential part in the development of preeclampsia.…”
Section: Discussionsupporting
confidence: 68%
“…It limited the venous return, so measuring IAP could be useful in prenatal care. Similarly, the findings confirmed by pre-eclampsia study Marshalov, et al, (2016) in which the data was a large representative sample of "more than six hundred" patients at various stages of gestation and demonstrated that an increase in intra-abdominal pressure at 20-24 weeks of pregnancy preceded the development of preeclampsia with significantly as higher than regular patients (p <0.001) and the rate of its elevation considered as an essential part in the development of preeclampsia.…”
Section: Discussionsupporting
confidence: 68%
“…Some Authors have reported that IAH can cause venous congestion, hypertension, hypoperfusion, and systolic cardiac dysfunction [ 2 , 5 , 10 13 ], and multiple organs dysfunction similar to that seen in pre-eclampsia (PE) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies [ 2 , 10 , 11 , 15 18 ] have observed the effects of IAH on adverse maternal-fetal outcomes, the assessment of IAP during pregnancy is underestimated and neglected [ 2 ]. Therefore, the present study aims to conduct a systematic review of the literature to assess the effects of IAH on maternal-fetal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors and immune factors have also been established as contributors to the development of preeclampsia. Additionally, increased IAP may serve as a contributing factor [ 5 ]. The extent of each factor’s contribution to the pathogenesis may vary depending on individual circumstances.…”
Section: Introductionmentioning
confidence: 99%